Gaps in knowledge among physicians regarding diagnostic criteria and management of polycystic ovary syndrome - Dokras, Anuja; Saini, Shailly; Gibson-Helm, Melanie; Schulkin, Jay; Cooney, Laura; Teede, Helena (Fertility and sterility, 2017)
To identify gaps in polycystic ovary syndrome (PCOS) knowledge and practice patterns among physicians in North America in response to significant dissatisfaction identified among women with PCOS regarding their diagnosis and treatment experience. Online survey conducted via American College of Obstetrics and Gynecology of gynecologists (ObGyn) and American Society of Reproductive Medicine of reproductive endocrinologists (REI-ObGyn) in 2015-16. Not applicable. None. None. Diagnostic criteria used, key features of PCOS, management practices. Of the 630 surveys completed, 70.2% were ObGyn and 64.4% were females. Overall 27.7% respondents did not know which PCOS diagnostic criteria they used. In a multivariable analysis including physician type, age, gender, and number of patients with PCOS seen annually, REI-ObGyn were less likely compared with ObGyn to report not knowing which criteria they used (adjusted odds ratio, 0.08; 95% confidence interval, 0.04, 0.16). REI-ObGyn were more likely to use the Rotterdam criteria (odds ratio, 2.26; 95% confidence interval, 1.33, 3.82). The majority of respondents recognized the clinical features associated with PCOS; however, over one-third associated "cysts on ovaries" with PCOS. The majority of responders (>85%) were aware of cardiometabolic comorbidities; however, fewer ObGyn were aware of associated depression, anxiety disorders, and reduced quality of life. More REI-ObGyn recommended lifestyle changes compared with ObGyn (56.4% vs. 41.6%). Our large-scale PCOS survey, conducted in response to patient concerns regarding diagnosis and treatment, highlights opportunities for physician education. Focus areas include targeting knowledge of internationally accepted Rotterdam criteria and ensuring consistent care informed by evidence-based guidelines across the reproductive, metabolic, and psychological features of PCOS.